The Impact of the Complexity of Information Systems on User Performance Case of Moroccan Companies (International Journal of Scientific Research and Management (IJSRM), 2023)
The literature review highlights that the complexity of information systems increases with the increase in size and with the decrease in the percentage of family actions within the company, as well as having a highly trained leader. An analysis of previous works shows that several researchers have used the criterion of the degree of complexity to characterize information systems. The first objective of our research is to assess the influence of the degree of complexity of information systems on the frequency of their use. We will then examine the impact of this frequency on the overall work performance of information system users. However, we conducted a questionnaire survey and we were able to analyze just the responses of 49 companies. Given that the objective of our research is to examine the influence of the degree of complexity of information systems on the frequency of use and to assess the impact of this frequency on the performance of users, and in order to confirm or refute our research hypotheses, we conducted a data analysis using IBM SPSS Statistics 25.0 software, which allows us to perform the chi-square independence test to determine the existence of a relationship between the qualitative variables. Our results prove the significant impact of the degree of complexity of information systems - defined by the quality of its functionalities, its outputs and its flexibility - on the frequency of use. They also highlight the influence of this frequency on user performance defined by speed, productivity and response to work needs. Our study has limitations that open research perspectives in the future. Taking into account the national aspect of our study, it would be interesting to understand our results in different cultural areas with more qualitative devices and with a larger sample.